Perancangan Identitas Visual dan Media Promosi UMKM Novita Online Shop untuk Meningkatkan Brand Awareness - Putu Dewangga Widiawan Bandhesa; Ni Wayan Nandaryani; I Gede Yudha Pratama (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study aims to design a visual identity and promotional media that effectively enhances the brand awareness of Novita Online Shop, a micro, small, and medium enterprise (MSME). Currently, Novita Online Shop lacks a strong visual identity and effective promotional tools to boost consumer awareness. Through observations and interviews with the MSME owner, it was found that Novita Online Shop requires a visual identity and promotional media that can increase consumer awareness and differentiate the brand from its competitors. The concept of "Fresh Minimalism with Trendy Simplicity" was adopted as the foundation for developing the visual identity and promotional media. The findings indicate that designing an effective visual identity and promotional materials can improve consumer awareness, distinguish the brand from competitors, and ultimately drive sales. This study can serve as a reference for other MSMEs in creating effective visual identities and promotional strategies to enhance brand awareness.